Safety and Efficacy of Ketamine Versus Ketamine-Fentanyl-Dexmedetomidine Combination for Anesthesia and Analgesia in Rats - Chunzhu Li; Jiali Peng; Rong Hu; Jia Yan; Yu Sun; Lei Zhang; Wenbin Liu; Hong Jiang (SAGE Publishing, 2019)
Ketamine (KET), a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, is most frequently used as an anesthetic, analgesic, and sedative drug in pediatric clinical practices. However, the adverse effects of KET administration such as psychotic episodes limited the use of KET. The aim of the present study was to evaluate whether the addition of small doses of fentanyl (FENT) and dexmedetomidine would reduce the overall KET consumption without concession on the safety and efficacy of anesthesia and analgesia in rats. We compared the effects of KET (50 mg/kg) administration alone and KET (25 mg/kg) combined with FENT (0.005 mg/kg) and dexmedetomidine (0.05 mg/kg) (KFD) on the times of onset and duration of anesthesia and analgesia. Compared with the KET group, the KFD group provides similar onset time of anesthesia, but longer duration of anesthesia, and better analgesic effect. Unlike the KET group, the KFD group had a lower heart rate and higher respiratory rate. Meanwhile, KFD induced markedly changes in the electroencephalography (EEG) spectral power when compared with control and KET. Furthermore, combination of FENT and dexmedetomidine alleviated the liver toxicity of KET. These results indicated that, when compared with KET alone, the administration of KFD combination offered safer and more efficient anesthesia.